A Dual‐Administration Microtracer Technique to Characterize the Absorption, Distribution, Metabolism, and Excretion of [14C]Seletalisib (UCB5857) in Healthy Subjects. (26th June 2017) - Helmer, Eric; Nicolas, Jean‐Marie; Long, Jeff; Roffel, Ad F.; Jones, Emma; Chanteux, Hugues; Diaz, Nieves; Garratt, Holly; Bosje, Tjerk
Abstract: Phosphoinositide 3 kinases are targets for development of small‐molecule inhibitors to disrupt progression of immune‐inflammatory diseases. This phase 1 open‐label study (Eudract 2014‐005353‐39) evaluated the safety and relative bioavailability of 2 new seletalisib (UCB5857) formulations (A and B) compared with a reference formulation. Absolute bioavailability (period 1a, n = 6) and disposition and metabolism (period 1b, n = 6) of the reference formulation were evaluated: healthy subjects received 30 mg orally plus ∼20 μg of a 14 C‐labeled microtracer (intravenously in 1a, orally in 1b). New formulations were evaluated: subjects from periods 1a and 1b were pooled and randomly distributed to receive a single oral dose (30 mg) of formulation A (n = 6) or B (n = 6) in periods 2 and 3, using a crossover design. Absolute oral bioavailability of seletalisib was 97% (90% confidence interval 87, 107). Unchanged [ 14 C]seletalisib was the predominant radioactive component in plasma (94.8%). After oral dosing, the radioactive dose was primarily recovered in feces (74.6%, geometric coefficient of variation [GeoCV] 18.1%), mostly as metabolites. Seletalisib demonstrated a 24‐hour terminal half‐life, volume of distribution of 60.9 L (GeoCV 23.8%), and a total plasma clearance of 1.7 L/h (GeoCV 35.4%). Formulations A and B displayed similar or even higher exposure compared with reference seletalisib (areas under the concentration‐time curves 19 337 [GeoCV 30.8%], 20 380 [GeoCV 37.7%], and 15 932 [GeoCV 36.4%] h·ng/mL, respectively). New formulations A and B were bioequivalent with each other, and all 3 formulations showed acceptable safety profiles. This radiolabeled microtracer approach successfully informed on the absorption, distribution, metabolism, and excretion of seletalisib and further guided the mechanistic pharmacokinetic modeling.